The Questions of Economics History and Methodology - Larkina, Tatyana (Journal of Economic Sociology, 2016)
The “Economic Methodology” section under the moderation of HSE Professor Vladimir Avtonomov took place on the 20th and 21st of April within the XVII April International Academic Conference on Economic and Social Development. The section consisted of five sessions: “Economics: Beginning and Continuation”; “Soviet Theorists and Historians of Thought”; “Property, Inequality, Paternalism”; “Methodological Problems of Economic Science”; and “In Search of a Realistic Economics.” Each session had three reports which were followed with discussion among the participants. The question of theoretical and methodological nature of economics and history of economic thought as well as the problem of the practical application of theoretical knowledge were in the spotlight. This paper focuses on a philosophical and methodological reflection of economics and the history of economic thought, and it partly stresses the problems and practical application of economic knowledge; therefore, not all reports are discussed. Economics is an unrealized natural science project in which primordial foundation has a moral character and is associated with philosophical notions about economy life organization. Scholars’ comprehension of economics, its methodology, and models of economic human has changed over the years. Economists, historians, and methodologists of economic thought reference the philosophical theories and concepts, which allow them to look critically at what is happening inside the disciplinary area, resolve old problems, and ask new questions.